Pneumococcal conjugate and plain polysaccharide vaccines have divergent effects on antigen-specific B cells. - Clutterbuck, E; Lazarus, R; Yu, L; Bowman, J; Bateman, E; Diggle, L; Angus, B; Peto, T; Beverley, P; Mant, D; Pollard, A (2012)
BACKGROUND: A 23-valent unconjugated pneumococcal polysaccharide vaccine (23vP), routinely administered at the age of 65, has limited effectiveness, and revaccination induces attenuated antibody responses. It is not known whether pneumococcal polysaccharide-protein conjugated vaccines (PCV), although highly effective in infants, offer any immunological advantages over 23vP in adults. METHODS: We immunized adults with schedules combining both PCV and 23vP and investigated B-cell responses to establish whether PCV7 (a 7-valent PCV) induced T-dependent responses in adults, to assess the role of memory B cells in 23vP-induced antibody hyporesponsiveness, and to identify the B-cell subtypes involved. RESULTS: A single dose of PCV7 induced significant increases in serotype-specific memory B-cell populations in peripheral blood indicating a T-dependent response. Conversely, immunization with 23vP resulted in a decrease in memory B-cell frequency. Furthermore, memory B-cell responses to subsequent immunization with PCV7, when given after 23vP, were attenuated. Notably, B1b cells, a subset important in protecting mice against pneumococci, were also depleted following immunization with 23vP in humans. CONCLUSIONS: This study indicates that PCV7 may have an immunological advantage over 23vP in adults and that 23vP-induced depletion of memory and B1b-cell subsets may provide a basis for antibody hyporesponsiveness and the limited effectiveness of 23vP. Clinical Trials Registration. ISRCTN: 78768849.